Emotional Intelligence & ICTs for Women and Equality - Papoutsi, Chara; Chaidi , Irene; Drigas, Athanasios; Skianis, Charalabos; Karagiannidis, Charalampos (Technium Social Sciences Journal, 2022)
Gender equality is a fundamental human right and is essential for the existence of peaceful societies, with human resources that are fully utilized and sustainable development. Emotional Intelligence is not gender biased and it is an integral key to successful personal and working life. In (Drigas & Papoutsi, 2021) there was an attempt to construct a reliable and valid measurement instrument of emotional intelligence with 81 items, based on the theoretical nine-layer pyramid model of emotional intelligence. The sample was consisted of 520 teachers (129 males and 391 females) from primary and secondary school grade and the data was collected with the Nine Layer Pyramid Model Questionnaire for Emotional Intelligence. Among other results we examined gender differences in emotional intelligence. The results revealed some differences between the two genders on emotional intelligence with women scoring higher on overall emotional intelligence. This article also provides an overview of the prevailing emotional intelligence status of both sexes as it emerges through research, beliefs about emotions between women and men, and suggestions for avoiding stereotypes and proper interventions for raising emotional both men and women. Finally, a reference is made to technology in its various forms, including Information and Communication Technology (ICT), which is also associated with emotional intelligence and has great potential to empower women worldwide and promote gender equality